Sustainable Investing in Emerging Markets: Evidence from an Extended TPB Approach - Deane Rahmamita; Fikri Hizryan (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to analyze the factors influencing green investment intention and behavior in the context of a developing country, particularly Indonesia, by employing an extended Theory of Planned Behavior (TPB) framework. Specifically, this study examines the effects of attitude, subjective norms, and perceived behavioral control on green investment intention, as well as the effects of intention and income on green investment behavior. In addition, income is examined as a moderating variable in the relationship between green investment intention and green investment behavior. Data were collected through an online survey of 155 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that attitude, subjective norms, and perceived behavioral control have positive and significant effects on green investment intention. Green investment intention is found to be the main predictor of green investment behavior. Income does not have a significant direct effect on green investment behavior; however, it significantly strengthens the effect of intention on green investment behavior. The R-square values show that the model explains 65.8% of the variance in green investment intention and 34.7% of the variance in green investment behavior. These findings confirm the relevance of the TPB in explaining green investment behavior and demonstrate that structural factors, such as financial capacity, remain important in determining the extent to which intention can be translated into actual behavior. This study provides implications for policymakers and financial industry practitioners in designing green investment products that are more inclusive, accessible, and aligned with individuals’ financial capacity.